The grip book - Uva, Michael (Focal Press, 2010)
The Grip Book, Fourth Edition has been updated and revised to be even more valuable to professional grips-the "jack-of-all-trades and master of all" on a film or video set. Grips install, set up, maintain, and ensure the safety of all equipment needed on a set, such as lighting stands, cameras, and any specialty equipment needed for a shoot. This new edition contains the latest information about the latest equipment and has been updated to reflect changes in the industry including CGI screen setup and 'cleaning up the perms.' The Grip Book also teaches readers how to become a professional grip and have a successful career, and will continue to be an indispensable learning tool and reference for grips of all experience levels. * Known as "the bible" for grips on TV and movie sets, professionals know it and love this well-respected and heavily-illustrated classic from a knowledgeable and well-known author and grip * Includes a website with visual demonstration videos and hundreds of illustrations help clarify and demonstrate concepts * Covers new topics such as CGI screens and perms and includes a slew of new glossary terms and slang words that all grips need to know